Primary bilateral guttural pouch empyema in a two-month-old foal - Dias, Deborah Penteado Martins [UNESP]; Bernardi, Nara Saraiva [UNESP]; Queiroz, Daniela Junqueira de [UNESP] (Universidade Federal de Santa Maria, 2015)
The present report describes a 2-month-old foal which signs of respiratory infectious disease, bilateral retropharyngeal swelling and nasal mucopurulent discharge, suggesting guttural pouch empyema. The owners reported that the foal lived in a herd that experienced an outbreak of strangles. Foals younger than 3 months are usually protected against infectious diseases, however in this case, the foal was exposed to an environment heavily populated by Streptococcus equi equi during the outbreak of strangles. Although uncommon in such young animals, the foal was infected and developed a primary bilateral guttural pouch empyema, without signs of lymph nodes alteration

O presente trabalho descreve o caso de um potro de dois meses de idade com sinais de infecção respiratória, distensão bilateral da região retrofaríngea e secreção nasal mucopurulenta, sugerindo empiema de bolsa gutural. Os proprietários relataram que o potro pertencia a uma tropa que havia sido acometida por garrotilho recentemente. Potros com menos de 3 meses de idade são normalmente protegidos contra as doenças infecciosas, no entanto, este potro foi exposto a um ambiente altamente contaminado por Streptococcus equi equi durante o surto de garrotilho. Embora incomum em animais tão jovens, o potro foi infectado e desenvolveu um empiema primário de bolsa gutural, não havendo sinais de acometimento dos linfonodos
Empiema de bolsa gutural primário bilateral em potro de dois meses
Keywords: Guttural pouch; Horse; Strangles; Streptococcus equi; Bolsa gutural; Equino; Garrotilho; Streptococcus equi